Banking awareness and its impact on achieving sustainable banking - عادل عباس عبد الحسين الجنابي; فاطمة عباس أحمد (Iraqi Journal for Administrative Sciences, 2024)
The aim of the study is to study the issue of banking awareness and its impact on achieving sustainable banking. Banking awareness is to explore how customers can create knowledge about products and services and the lack of information and services. Sustainable banking means the social responsibility that the World Bank has defined as the concept of corporate social responsibility as the commitment of business owners to contribute In sustainable development. The questionnaire was used to measure the study variables. The study sample consisted of (60) workers from a society of 120. The study was based on three hypotheses, the most important of which is that there is no significant effect between banking awareness and sustainable banking. The descriptive statistics and the analytical statistics were used. Some statistical methods were used, the most important of which were frequencies, percentages, weighted arithmetic, and standard deviations. The choice of t was used, regression equations, R values and F values were used. The research data were collected by means of the questionnaire and were analyzed mathematically by using the statistical statistics coefficients and were implemented using the statistical program (SPSS.V.21). The researcher reached a number of conclusions, the most important of which was: - There is a statistically significant relationship between banking awareness and sustainable banking. The researcher recommended the need to pay attention to customer satisfaction through banking awareness as well as interest in the implementation of sustainable banking activities.